Graduate Students’ Perceptions and Practices on the Use of ICT for Promoting Learning Autonomy - Karunia Eka Nafilatul Janah; Pratiwi Retnaningdyah; Ali Mustofa (Pascasarjana Universitas Negeri Makassar, 2022)
Some previous studies have proven that the use of ICT for learning gives some benefits as well as challenges for promoting learning autonomy. Thus, this research is aimed at investigating graduate students’ perceptions and practices on the use of ICT for promoting learning autonomy during the Covid-19 pandemic as well as the opportunities and challenges. This research employed a case study of qualitative research design involving ten graduate students of a state university in Surabaya. The data of this research is collected through an online questionnaire. This research revealed that all graduate students involved in this research have been familiar with the term ‘ICT’ and ‘learning autonomy’ in general. Furthermore, they have positive perceptions on the use of ICT for promoting learning autonomy during the Covid-19 pandemic. In addition, the technologies and applications that they utilize during the Covid-19 pandemic are Google apps, LMS (Learning Management System), Reference Management Software (RMS), electronic devices, etc. Then, they also experience some opportunities which are getting to know applications, websites, and tools to support their learning, providing up to date materials, articles, information, and resources or references for their learning, and helping them to communicate or interact with their teachers and classmates. Finally, the challenges that they experience are internet connection problem, unnecessary or unclear information & irrelevant contents that make them unfocused or distracted, and problem in operating the applications or devices.